SOCIO- PSYCHOLOGICAL ASPECTS OF LEADERSHIP - Xasanova Iroda (Scholar Express Journals, 2023)
The article presents the socio-psychological characteristics of the ability of a leader-researcher. The necessary aspects of a manager in management are also theoretically analyzed
Keywords: management; generation with mature; intellectual potentia